Produktives Fördern im inklusiven Mathematikunterricht - Häsel-Weide, Uta; Nührenbörger, M. (Inklusives Lehren und Lernen von Mathematik: Konzepte und Beispiele mit Fokus auf Grund- und Förderschule)

Achsensymmetrisch?! Praktiken, soziale und sozio-mathematische Normen der Begründung der Achsensymmetrie ebener Figuren in der Grundschule - Häsel-Weide, Uta; Wallner, Melina (Journal für Mathematik-Didaktik)

Using academic mathematical knowledge when working on interface tasks–analyses of pre-service teachers’ arguments about rotationally symmetric figures - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Abstract Special tasks for pre-service teachers (PSTs) in university mathematics courses (“interface tasks”) are a common innovation in recent years to overcome the second discontinuity. By this, we mean tasks that are situated by typical everyday challenges of mathematics teaching and in which PSTs must use their mathematical knowledge and skills in a professionally relevant way. In this paper, we analyze answers that PSTs have created to an interface task on symmetry. The PSTs were asked to clarify a student’s question from a mathematical perspective and then give a suitable elementarized answer. We situate these two steps theoretically and reconstruct the mathematical reasoning in PSTs' answers. Through qualitative content analysis, we examined how PSTs justify figures' symmetries from a university mathematics perspective and when responding to the fictitious student. The scenario of a student questioning the existence of 100° rotationally symmetrical figures elicited rich and varied responses, proving suitable for an interface task. We compared PSTs' reasoning related to mathematical clarification with the reasoning related to elementarization. In many cases, this revealed a productive use of course content. An interesting result is that there is no uniform picture as to whether the arguments are more detailed in the mathematical clarification or in the elementarization.

Manifolds of absolutely continuous functions with values in an infinite-dimensional manifold and regularity properties of half-Lie groups - Pinaud, Matthieu

Lernvideos in der Mathematik – Beiträge zur Abschlusstagung des Projektes studiVEMINTvideos der Universität Paderborn und der TH Köln

Dunkl convolution and elliptic regularity for Dunkl operators - Brennecken, Dominik (Mathematische Nachrichten)
Abstract We discuss in which cases the Dunkl convolution of distributions , possibly both with non‐compact support, can be defined and study its analytic properties. We prove results on the (singular‐)support of Dunkl convolutions. Based on this, we are able to prove a theorem on elliptic regularity for a certain class of Dunkl operators, called elliptic Dunkl operators. Finally, for the root system we consider the Riesz distributions and prove that their Dunkl convolution exists and that holds.

Critically 3-frustrated signed graphs - Cappello, Chiara; Naserasr, Reza; Steffen, Eckhard; Wang, Zhouningxin (Discrete Mathematics)

Curvature and stability of quasi-geostrophic motion - Suri, Ali (Journal of Geometry and Physics)

Conjugate points along spherical harmonics - Suri, Ali (Journal of Geometry and Physics)

L^1-regularity of strong ILB-Lie groups - Glöckner, Helge; Suri, Ali

New trends in didactic research in university mathematics education - Biehler, Rolf; Durand-Guerrier, Viviane; Trigueros, María (ZDM – Mathematics Education)
Abstract Recent research in university mathematics education has moved beyond the traditional focus on the transition from secondary to tertiary education and students' understanding of introductory courses such as pre-calculus and calculus. There is growing interest in the challenges students face as they move into more advanced mathematics courses that require a shift toward formal reasoning, proof, modeling, and problem-solving skills. This survey paper explores emerging trends and innovations in the field, focusing on three key areas: innovations in teaching and learning advanced mathematical topics, transitions between different levels and contexts of mathematics education, and the role of proof and proving in advanced university mathematics. The survey reflects the evolving landscape of mathematics education research and addresses the theoretical and practical challenges of teaching and learning advanced mathematics across various contexts.

Operative Beziehungen erkennen, beschreiben und nutzen – Initiierung von Lernprozessen unter Einbeziehung der App ‚Rechenfeld‘ - Dettelbach, Andrea; Häsel-Weide, Uta (Förderung prozessbezogener Kompetenzen mit digitalen Medien. Mit mathematischen Objekten und Werkzeugen arbeiten)

Der Einzug der Mathematik in die Bildungspläne der höheren Mädchenschulen zu Beginn des 20. Jahrhunderts - Werth, Gerda (Beiträge zum Mathematikunterricht 2024)

Data and Social Worlds: How Data Science Education Supports Civic Participation and Social Discourse - Miller, Katherine M; Polman, Joseph L; Yoon, Susan A; Shim, Jooeun; Leung, Vivian Y; Nguyen, Yen; Rubin, Andee; Higgins, Traci; Karch, Jessica M; Hammerman, James KL; Matuk, Camillia; DesPortes, Kayla; et al. (Proceedings of the 18th International Conference of the Learning Sciences-ICLS 2024)

Symplectic Methods in Deep Learning - Maslovskaya, Sofya; Ober-Blöbaum, Sina (IFAC-PapersOnLine)

Inverse optimal control problem in the non autonomous linear-quadratic case - Jean, Frédéric; Maslovskaya, Sofya

Personalizing real‐world problems: Posing own problems increases self‐efficacy expectations, intrinsic value, attainment value, and utility value - Schönherr, Johanna (British Journal of Educational Psychology)
Abstract Background Real‐world problems are important in math instruction, but they do not necessarily trigger students' task motivation. Personalizing real‐world problems by (1) matching problems to students' shared living environment (context personalization) and (2) asking students to pose their own problems (active personalization) might be two interventions to increase students' task motivation. Aim In the current study, we investigated the effects of context personalization and active personalization on students' self‐efficacy expectations, intrinsic value, attainment value, utility value, and cost. Sample The participants were 28 fifth‐ and sixth‐grade students who voluntarily took part in a six‐month afterschool program in which they posed problems with the aim of creating a math walk in their hometown. Method Using a within‐subjects design, at the end of the afterschool program, the students rated their self‐efficacy expectations and task values for four self‐developed problems associated with their hometown, four peer‐developed problems associated with their hometown, and four instructor‐provided problems associated with unfamiliar locations. Results Students reported higher self‐efficacy expectations, intrinsic value, attainment value, and utility value for active‐personalized than non‐personalized problems. To a lesser extent, context personalization promoted intrinsic value and attainment value. No effect was found for cost. Conclusions Active personalization (i.e. asking students to pose their own real‐world problems) is suited to enhance students' task motivation, specifically their self‐efficacy expectations, intrinsic value, attainment value, and utility value. Context personalization still boosts students' intrinsic value and attainment value. Implementation in classroom instruction is discussed.

Preservice teachers' judgments of students’ expectations of success and task values: Close relations with their personal task motivation - Schönherr, Johanna; Schukajlow, Stanislaw (Teaching and Teacher Education)

Learning with visualizations helps: A meta-analysis of visualization interventions in mathematics education - Schönherr, Johanna; Strohmaier, Anselm R.; Schukajlow, Stanislaw (Educational Research Review)

Anxiety Moderates the Effects of Drawing Support on Drawing Accuracy in Mathematical Modeling - Schönherr, Johanna; Mayer, Richard E. (Lecture Notes in Computer Science)